2002
DOI: 10.1093/molehr/8.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and embryonic regulation of chemokines IL-8, MCP-1 and RANTES in the human endometrium during the window of implantation

Abstract: Chemokines are a family of small polypeptides which specialize in the attraction of leukocytes. The presence of specific leukocyte subsets at the implantation site is an important element of the complex, and not completely understood, process of embryonic implantation. This report includes the investigation of the in-vivo immunolocalization and hormonal regulation of interleukin (IL)-8, monocyte chemotactic protein (MCP)-1 and RANTES (regulated upon activation normal T-cell expressed and secreted) in the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 40 publications
5
79
0
3
Order By: Relevance
“…Based on our proposed model, it is conceivable that UDPglucose may be released from these apoptotic endometrial epithelial cells, which, in turn, may activate P2RY14 in a paracrine/ autocrine manner, leading to IL-8 production. Consistent with our hypothesis, Caballero-Campo et al (49) demonstrated using in vitro coculture experiments that both IL-8 mRNA expression and protein production were up-regulated in endometrial epithelial cells in the presence of a human blastocyst. In both menstruation and implantation, IL-8 production and infiltrated neutrophils may play a role in the angiogenesis for endometrial remodeling/regeneration, trophoblast invasion, and placentation, rather than prevention of the progression of infection (50).…”
Section: Discussionsupporting
confidence: 92%
“…Based on our proposed model, it is conceivable that UDPglucose may be released from these apoptotic endometrial epithelial cells, which, in turn, may activate P2RY14 in a paracrine/ autocrine manner, leading to IL-8 production. Consistent with our hypothesis, Caballero-Campo et al (49) demonstrated using in vitro coculture experiments that both IL-8 mRNA expression and protein production were up-regulated in endometrial epithelial cells in the presence of a human blastocyst. In both menstruation and implantation, IL-8 production and infiltrated neutrophils may play a role in the angiogenesis for endometrial remodeling/regeneration, trophoblast invasion, and placentation, rather than prevention of the progression of infection (50).…”
Section: Discussionsupporting
confidence: 92%
“…The proper development of the maternal decidua and the molecular cross-talk between the decidua and the fetal trophoblast are of paramount importance for blastocyst invasion into the endometrium, implantation, and successful pregnancy. The importance of the endometrial stroma in this cross-talk resides in the fact that steroid hormones target endometrial stromal cells, which in turn facilitate the interaction between the blastocyst and the uterine epithelium (Ghosh & Sengupta 1998, Caballero-Campo et al 2002, Bourdiec et al 2013). …”
Section: The Role Of the Decidua In Human Pregnancymentioning
confidence: 99%
“…During the window of receptivity, steroid hormones facilitate the interaction between the blastocyst and the uterine epithelium via the endometrial stroma (Ghosh & Sengupta 1998, Caballero-Campo et al 2002, Bourdiec et al 2013. Therefore, an altered pattern of expression of their receptors in the decidua could well have a negative impact on female fertility, especially on the success of implantation.…”
Section: Effect Of Bpa On Secretion Of Biomarkers Of Endometrial Matumentioning
confidence: 99%
“…Medical Immunology Медицинская Иммунология хемоатрактантом для моноцитов и макрофагов, а также для Т-лимфоцитов и NK-клеток, которые мигрируют в децидуальную ткань матки из пери-ферической крови в течение беременности [5]. Повышенная секреция этого хемокина клетками линии ТНР-1 может свидетельствовать о потен-циальной возможности мигрирующих в деци-дуальную ткань моноцитов, а также макрофагов децидуальной ткани и ткани плаценты секрети-ровать МСР-1 в первом триместре беременности, обеспечивая адекватное аккумулирование клеток иммунной системы матери в децидуальной обо-лочке.…”
Section: Discussionunclassified
“…Гестоз со-провождается нарушением формирования ткани плаценты и усиленной продукцией провоспали-тельных цитокинов [28], способных активировать моноциты и стимулировать усиленную секрецию MCP-1 макрофагами децидуальной оболочки и ткани плаценты. Под действием MCP-1 моно-циты, макрофаги, Т-лимфоциты и NK-клетки матери мигрируют в децидуальную ткань и ткань плаценты [5], усиливая мононуклеарную ин-фильтрацию и способствуя развитию местной воспалительной реакции, характерной для гесто-за. Хотя секреция IL-6 клетками линии ТНР-1 была повышена в присутствии секреторных продуктов ткани плацент женщин с гестозом по сравнению со здоровыми беременными, она оставалась на достаточно низком уровне.…”
Section: Discussionunclassified